2017
DOI: 10.1038/nrdp.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constipation

Abstract: Chronic constipation is a prevalent condition that severely impacts the quality of life of those affected. Several types of primary chronic constipation, which show substantial overlap, have been described, including normal-transit constipation, rectal evacuation disorders and slow-transit constipation. Diagnosis of primary chronic constipation involves a multistep process initiated by the exclusion of 'alarm' features (for example, unintentional weight loss or rectal bleeding) that might indicate organic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
232
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(254 citation statements)
references
References 207 publications
4
232
1
17
Order By: Relevance
“…Despite normal transit constipation being the most prevalent subgroup of CIC, the pathophysiology remains unclear 23 . Changes in the colonic microbiota can increase bile acid metabolism, 24 promote methane production 25 and affect epithelial function, all of which can alter colonic motility and fluid secretion, resulting in constipation 26 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Despite normal transit constipation being the most prevalent subgroup of CIC, the pathophysiology remains unclear 23 . Changes in the colonic microbiota can increase bile acid metabolism, 24 promote methane production 25 and affect epithelial function, all of which can alter colonic motility and fluid secretion, resulting in constipation 26 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…A study in patients with IBS found that increased physical activity improved gastrointestinal symptoms and was also protective against a deterioration in symptoms, 63 effects which might be mediated through positive effects on anti‐inflammatory and anti‐oxidant pathways, as well as immune function 64 . In CIC specifically, although intervention programs to increase physical activity may be of some help in older patients, 62 there is no evidence to suggest that increasing levels of physical activity in younger people is beneficial 23 …”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of participants in our survey who experienced abdominal pain besides constipation, and who could therefore be considered close to the IBS‐C spectrum could explain the higher number of doctor visits in this study. A subgroup of patients with constipation, more specifically those with normal‐transit constipation have been reported to overlap considerably with IBS‐C . No specification of transit data was available for the current epidemiological study; however, normal‐transit constipation is thought to make up the largest group of constipated patients.…”
Section: Discussionmentioning
confidence: 99%